A unifying conceptual framework of factors associated to cardiac vagal control. Issue 12 (December 2018) - Laborde, Sylvain; Mosley, Emma; Mertgen, Alina
Abstract: Cardiac vagal control (CVC) reflects the activity of the vagus nerve regulating cardiac functioning. CVC can be inferred via heart rate variability measurement, and it has been positively associated to a broad range of cognitive, emotional, social, and health outcomes. It could then be considered as an indicator for effective self-regulation, and given this role, one should understand the factors increasing and decreasing CVC. The aim of this paper is to review the broad range of factors influencing CVC, and to provide a unifying conceptual framework to integrate comprehensively those factors. The structure of the unifying conceptual framework is based on the theory of ecological rationality, while its functional aspects are based on the neurovisceral integration model. The structure of this framework distinguishes two broad areas of associations: person and environment, as this reflects adequately the role played by CVC regarding adaptation. The added value of this framework lies at different levels: theoretically, it allows integrating findings from a variety of scientific disciplines and refining the predictions of the neurovisceral integration model; methodologically, it helps identifying factors that increase and decrease CVC; and lastly at the applied level, it can play an important role for society regarding health policies and for the individual to empower one's flourishing.